2019
DOI: 10.1111/jth.14446
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular and bleeding outcomes in a population‐based cohort of patients with chronic immune thrombocytopenia

Abstract: Background: Among patients with chronic immune thrombocytopenia (cITP), little is known regarding risk factors for cardiovascular and bleeding outcomes and how these events influence mortality. Objectives:We examined the rate of cardiovascular events and bleeding requiring a hospital contact according to platelet count levels, as well as the prognostic impact of these events on all-cause mortality in adult patients with cITP. Methods: We identified all cITP patients registered in the Nordic Country PatientRegi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
47
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 41 publications
1
47
0
5
Order By: Relevance
“…These data illustrate that ITP is a serious and occasionally a fatal disease. A recent study showed that in chronic ITP, a platelet count <25 × 10 9 /l was associated with a 7‐ and 4·5‐fold increase in the risk of haemorrhage requiring hospitalization at respectively one and five years, as compared to ITP patients with normal platelet counts 11 . It also showed that the risk of death was markedly higher among patients with a bleeding event requiring a hospital contact.…”
Section: Discussionmentioning
confidence: 99%
“…These data illustrate that ITP is a serious and occasionally a fatal disease. A recent study showed that in chronic ITP, a platelet count <25 × 10 9 /l was associated with a 7‐ and 4·5‐fold increase in the risk of haemorrhage requiring hospitalization at respectively one and five years, as compared to ITP patients with normal platelet counts 11 . It also showed that the risk of death was markedly higher among patients with a bleeding event requiring a hospital contact.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to ITP patients with normal platelet counts, those with a platelet count between 25 to 49 × 10 9 /L and <25 × 10 9 /L had 2.4 fold and 4.5 fold increased bleeding rates, respectively [51]. Furthermore, bleeding requiring a hospital contact within 1 year prior to ITP diagnosis was associated with a 3-fold increased rate of subsequent bleeding [51]. The use of non-steroidal anti-inflammatory drugs (NSAIDs) was found to be associated with any bleeding (OR 4.8, 95% CI 1.1-20.7) and anticoagulant drugs were associated with severe bleeding (OR 4.3, 95% CI 1.3-14.1) [57].…”
Section: Clinical Manifestationsmentioning
confidence: 86%
“…Compared to ITP patients with normal platelet counts, those with a platelet count between 25 to 49 × 10 9 /L and <25 × 10 9 /L had 2.4 fold and 4.5 fold increased bleeding rates, respectively [51]. Furthermore, bleeding requiring a hospital contact within 1 year prior to ITP diagnosis was associated with a 3-fold increased rate of subsequent bleeding [51].…”
Section: Clinical Manifestationsmentioning
confidence: 98%
See 1 more Smart Citation
“…Overall, the NCPRR is a powerful tool to assess unsolved questions about ITP epidemiology like variations of incidences, rates of bleeding, thrombosis [9], infections and malignancies. Future pharmacoepidemiological studies are also eagerly awaited to assess in the real-world practice the exposure to ITP treatments as well as their efficacy and safety in the context of lack of comparative clinical trials in this rare disease.…”
mentioning
confidence: 99%